High-Security Multi-Slot Chaos Encryption With Dynamic Probability for 16-CAP PON - Shun han; Bo liu; Yaya mao; Jianxin Ren; Xiangyu wu; Xing xu; Lei Jiang; Jingyi Zhang; Jianye Zhao (IEEE Photonics Journal, 2020)
In this paper, a high-security chaos encryption with dynamic probability for 16-carrier-less amplitude/phase (CAP) PON is proposed by using two-layer chaos map with feedforward neural network-based XOR operator (FNNXOR). The inner chaotic map is divided into several time slots, and the key of each time slot is different and dynamically allocated by outer layer of 2-dimensional logistic adjusted sine (2D-LASM) map. And the 16-CAP signal is encrypted by (CCDM) and XOR operator to realize dynamic probability and flexible rate. The ONU checks out and compares the hash value sent by OLT, so as to achieve slot synchronization. A 4 Gb/s multi-slot chaos encrypted 16-CAP signal with dynamic probability is transmitted through a 25-km standard single mode fiber (SSMF). The proposed scheme has a high anti-hacking capability and good performance under key leakage. Compared with conventional chaos encrypted 16-CAP signals, the probabilistic shaped signals exhibit better tolerance towards low received optical power. These experimental results verify that the proposed approach is a promising candidate for encryption in access network systems.